Through The Hardship of Short Fiction Narration: Challenges of Finding The Voice - Yespanova, Assyl (Nazarbayev University School of Sciences and Humanities, 2020)
The main aim of this project is to investigate the concept of the author’s voice. The methodic includes the research of the theoretical framework of the construction of the voice and the actual creation of the short stories used as the tool for finding the writer’s voice. The voice in literature represents the rhetorical mixture of different literary devices such as tone, point of view and the word choice; however, it also operates on the author’s features of the identity. As part of the project the detailed analysis and close reading of the strong voices in short fiction narrative such as Nabokov’s in “Sign and Symbols” and Baldwin’s in “Sonny’s Blues” were provided. The voices in those stories represent the psychological reflections of the authors on their experiences. Thus, the voice also derives through the interconnectedness of the author and their attitude towards the story. Further, I tried to implement this experience of understanding Nabokov’s use of the voice as the tool to deliver the truth of the author and Baldwin’s distinct voice representing the connection of the past and present. Through creating the short stories “明 (aka) meaning ‘bright’” and “…and earth kept singing” I came to the conclusion that the voice is rather a summation of reflections of author’s identity and a tool to speak the truth of own. Although the literary devices are essential to define the way the story is written, the important ingredient to the way the story sounds is an author’s choice of way on how to express this voice. The difficult experiences and identities that create the inner truth of the author and lead them to the process of telling that particular story are the main components that create the unique voice for a particular narrative that should sound in a voice the writer has intended.